Japanese Noun Phrase on Twitter Trending Topic - Hermawan, Gede Satya (Jurnal Bahasa Asing, 2023)
This paper discussed a Japanese noun phrase as hashtag Twitter. The research was conducted by collecting data for 1 month in September 2022. The data is not limited to a single chunky noun phrase, but noun phrases as constituents are also discussed in this paper. The descriptive qualitative method will describe the meaning of the phrase, and syntax will be used to identify the structure. The results reflect the used noun phrased as a hashtag, created simply as structure, but complex as semantically. The single hashtag has a discourse meaning behind it. Other than that, founded a treatment spoken language as writing text, and the users naturally find the meaning behind of it. This kind of situation indicates a premature sign of spoken language can fully understand without syntax marker on it (the spoken language always pragmatically helped by gesture, expression, and intonation).